2001
DOI: 10.1203/00006450-200107000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Different Surfactant Preparations to Inactivation by Meconium

Abstract: A disease similar to acute respiratory distress syndrome may occur in neonates after aspiration of meconium. The aim of the study was to compare the inhibitory effects of human meconium on the following surfactant preparations suspended at a concentration of 2.5 mg/mL: Curosurf, Alveofact, Survanta, Exosurf, Pumactant, rabbit natural surfactant from bronchoalveolar lavage, and two synthetic surfactants based on recombinant surfactant protein-C (Venticute) or a leucine/lysine polypeptide. Minimum surface tensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
3
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(49 citation statements)
references
References 52 publications
1
42
3
3
Order By: Relevance
“…Pilot studies using intratracheal doses of 50 -200 mg/kg of exogenous pulmonary surfactant as well as a controlled, randomized clinical study showed improved oxygenation of neonates with MAS receiving repeated high doses of surfactant (3). However, modified natural surfactants containing hydrophobic surfactant proteins B (SP-B) and C (SP-C) were more sensitive to inactivation by meconium than synthetic surfactant preparations based on artificial peptides such as SP-C analogues or the simplified peptide KL 4 (4). Thus, development of surfactants that are resistant to inactivation might be useful (5).…”
mentioning
confidence: 99%
“…Pilot studies using intratracheal doses of 50 -200 mg/kg of exogenous pulmonary surfactant as well as a controlled, randomized clinical study showed improved oxygenation of neonates with MAS receiving repeated high doses of surfactant (3). However, modified natural surfactants containing hydrophobic surfactant proteins B (SP-B) and C (SP-C) were more sensitive to inactivation by meconium than synthetic surfactant preparations based on artificial peptides such as SP-C analogues or the simplified peptide KL 4 (4). Thus, development of surfactants that are resistant to inactivation might be useful (5).…”
mentioning
confidence: 99%
“…Several publications have demonstrated the meconium-inactivating effect on surfactants 7,12,20,[23][24][25] . However, there are a small number of investigations that studied the effects of replacement therapy using exogenous surfactants in animal models with MAS.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ventilation time greater than 30 minutes is associated with a high prevalence of pneumothorax and an elevated mortality in this animal model 28 . Herting et al 25 compared the inhibitory effects of meconium on several types of exogenous surfactants and demonstrated that the several surfactants react in a different way to inhibition by meconium, depending on the apoprotein type and concentration. In our experiment, we used a surfactant that was produced with a Brazilian technology by Instituto Butantan, the effectiveness of which had already been demonstrated for SDR treatment in premature rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the bubble is changed periodically between a maximum and a minimum diameter, thereby mimicking the cyclic area compression during respiration in the alveolus. The pressure in the bubble is constantly recorded, and as the diameter at the end point is preset, the surface tension at the minimum bubble size (␥ min ) can be calculated by using the law of Laplace (9). Under physiological circumstances a surface tension close to 0 is needed to prevent alveolar collapse at the end of expiration.…”
Section: Methodsmentioning
confidence: 99%